Minimally-Invasive Versus Abdominal Hysterectomy for Endometrial Carcinoma With Glandular or Stromal Invasion of Cervix - Jung, Jihee; Noh, Joseph J.; Choi, Chel Hun; Kim, Tae-Joong; Lee, Jeong-Won; Kim, Byoung-Gie; Bae, Duk-Soo; Lee, Yoo-Young (Frontiers in Oncology, 2021)
The purpose of the study was to evaluate the feasibility of laparoscopic approach versus laparotomy in endometrial cancer that extends to the cervix in the form of glandular extension and/or stromal invasion. A retrospective, single-center cohort study was conducted using data between 1995 and 2017 at an urban tertiary academic medical center. We identified patients who were diagnosed with endometrial cancer whose tumor involved the uterine cervix on final pathology. Operative and oncologic outcomes were compared between the patients who underwent minimally-invasive surgery (MIS) versus those who underwent laparotomy. A total of 282 patients with endometrial cancer were reviewed for the study. Among these patients, 76 patients underwent hysterectomy and surgical staging via MIS. There was no conversion from MIS to laparotomy. In the MIS group, shorter hospital stay (4.4 ± 2.3 days for MIS group vs. 7.1 ± 4.7 days for laparotomy group; p-value = 0.002) and less blood loss during the operations (228 mL vs. 478 mL, p-value < 0.001) were observed compared to the laparotomy group. The multivariate Cox regression analysis revealed that age at diagnosis, FIGO stage, histology grades, tumor size, lymph-vascular space invasion were independent prognostic markers for poor oncologic outcomes but the types of surgical approach (MIS vs. laparotomy) was not associated with it. The means by which colpotomy was performed (either intracorporeal or transvaginal) among the MIS group also did not affect patient survivals. Among the women with endometrial cancer that involved the uterine cervix, surgical treatment via MIS compared with laparotomy showed no difference in survival outcomes but better perioperative results. These findings support the use of MIS for these patient group.